Risks Of Sharia Commercial Bank In Indonesia: Analysis Of Internal And External Factors - Erlinda Kurnia Aufa; Cita Sary Dja'akum (Universitas Islam Negeri (UIN) Walisongo Semarang, 2019)
Purpose - This study aims to analyze the effect of inflation, gross domestic product (GDP), capital adequacy ratio (CAR), and financing to deposit ratio (FDR) to non performing financing (NPF) at Islamic Commercial Banks in Indonesia.Method - The research approach used is a quantitative approach. Determination of samples is done by purposive sampling method. The data used is secondary data, obtained from publication reports on the official website of each Sharia Commercial Bank, Bank Indonesia, and the Central Statistics Agency. The population in this study were all Islamic Commercial Banks registered in the Statistics of Islamic Banking in Indonesia for the period 2013-2017. Based on the specified criteria, five Sharia Commercial Banks were obtained as research samples. This study uses panel data regression analysis with the Fixed Effects Model approach which is processed through the Eviews 10 program.Result - The results of hypothesis testing show that partially Inflation has a positive but not significant effect on NPF, GDP has a significant negative effect on NPF, CAR has a negative but not significant effect on NPF, and FDR has a significant negative effect on NPF. Simultaneously inflation, GDP, CAR, and FDR have a significant effect on NPF.Implication - This study uses all data from commercial Islamic bank.Originality - This study analyzes the determining factors that influence financing risks from both internal and external factors.